Epithelial-Mesenchymal Transition Induces GSDME Transcriptional Activation for Inflammatory Pyroptosis - Jia, Chenqiang; Zhang, Zhuqing; Tang, Jun; Cai, Mei-Chun; Zang, Jingyu; Shi, Kaixuan; Sun, Yunheng; Wu, Jie; Shi, Hailei; Shi, Weiping; Ma, Pengfei; Zhao, Xiaojing; et al. (Frontiers in Cell and Developmental Biology, 2021)
GSDME is a newly recognized executor of cellular pyroptosis, and has been recently implicated in tumor growth and immunity. However, knowledge about the molecular regulators underlying GSDME abundance remains limited. Here, we performed integrative bioinformatics analyses and identified that epithelial-mesenchymal transition (EMT) gene signatures exhibited positive correlation with GSDME levels across human cancers. A causal role was supported by the observation that EMT dictated GSDME reversible upregulation in multiple experimental models. Mechanistically, transcriptional activation of GSDME was directly driven by core EMT-activating transcription factors ZEB1/2, which bound to the GSDME promoter region. Of functional importance, elevated GSDME in mesenchymally transdifferentiated derivatives underwent proteolytic cleavage upon antineoplastic drug exposure, leading to pyroptotic cell death and consequent cytokine release. Taken together, our findings pinpointed a key transcriptional machinery controlling GSDME expression and indicated potential therapeutic avenues to exploit GSDME-mediated inflammatory pyroptosis for the treatment of mesenchymal malignancies.